(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the work of Nicolo Giacomuzzi, a composer, virtuoso musician and talented author of poems that reflect the deepest motives and prototypes of Turkic traditional culture. The performance of kai (throat singing) by Nicolo Giacomuzzi, accompanied by the musical instrument kai-komus, resembles the music of the Altai-Sayan peoples (Altaians, Khakassians, Tuvans, and Shors). We hope that in the future the work of musicologist will clarify the technique of this talented musician. Perhaps Nicolo Giacomudzi, like the Shors kaichi, performs singing with his “chest”, that is, “with an open larynx, squeezing air out of his lungs with his diaphragm and stomach.” N. Giacomudzi is not only a composer and virtuoso musician, but also a talented author of poems that reflect the deepest motives and prototypes of the Turkic traditional culture. We offer for analysis a number of fragments from two works by this a uthor, translated into the Shor language from English: “Kurgan” and “Kara-por adym”, the musical performance of which was included in the compact disc prepared by N. Giacomudzi based on the ancient steppe cultures of the nomads Purun-Purun “ A long time ago “ (translated into Shor language by L. N. Arbachakova, editor and commentator of the lyrics on the I. A. Nevskaya CD). N. Giakomudzi’s work finds a wide response on the Internet, on media communication platforms, and on social networks, including among users representing modern Turkic peoples, and contributes to the popularization and preservation of their languages and culture.